The Impact of BKI-1294 Therapy in Mice Infected With the Apicomplexan Parasite Neospora caninum and Re-infected During Pregnancy - Winzer, Pablo; Imhof, Dennis; Anghel, Nicoleta; Ritler, Dominic; Müller, Joachim; Boubaker, Ghalia; Aguado-Martinez, Adriana; Ortega-Mora, Luis-Miguel; Ojo, Kayode K.; VanVoorhis, Wesley C.; Hemphill, Andrew (Frontiers in Veterinary Science, 2020)
Exposure of Neospora caninum tachyzoites to BKI-1294 in vitro results in the formation of long-lived multinucleated complexes (MNCs). However, in vivo treatment of BALB/c mice with BKI-1294 shortly after N. caninum infection during pregnancy was safe and profoundly reduced pup mortality and vertical transmission. We hypothesized that the formation of MNCs could trigger immune responses that contribute to BKI efficacy in vivo. In this study, mice were first vaccinated with a sublethal dose of N. caninum tachyzoites and were treated with BKI-1294. We then investigated the effects of these treatments after mating and re-infection during pregnancy. Effects on fertility, pup survival, vertical transmission, and parasite load in dams were evaluated. Cytokines in sera or splenocyte culture supernatants were assessed by either ELISA or the Luminex™ 200 system, and humoral immune responses against tachyzoite and MNC antigens were compared by ELISA, Western blotting and immunoproteomics. Our results showed that BKI-1294 treatment of live-vaccinated mice reduced the cerebral parasite load in the dams, but resulted in higher neonatal pup mortality and vertical transmission. In live-vaccinated mice, cytokine levels, most notably IFN-y, IL-10 and IL-12, were consistently lower in BKI-1294 treated animals compared to non-treated mice. In addition, comparative Western blotting identified two protein bands in MNC extracts that were only recognized by sera of live-vaccinated mice treated with BKI-1294, and were not found in tachyzoite extracts. We conclude that treatment of live-vaccinated mice with BKI-1294 influenced the cellular and humoral immune responses against infection, affected the safety of the live-vaccine, and decreased protection against re-infection and vertical transmission during pregnancy.